2021
DOI: 10.1128/mbio.02973-21
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations in Antarctic Protistan Communities Highlight Phytoplankton Diversity and Seasonal Dominance by a Novel Cryptophyte Lineage

Abstract: The climate-sensitive waters of the West Antarctic Peninsula (WAP), including its many fjords, are hot spots of productivity that support multiple marine mammal species. Here, we profiled protistan molecular diversity in a WAP fjord known for high productivity and found distinct spatiotemporal patterns across protistan groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 95 publications
0
7
0
9
Order By: Relevance
“…4A and B ). To better understand the relationship between the microbial guilds of Lake Cadagno, we sought phylogenetic evidence to support the origin of these putative chloroplast OTUs, as described in previous literature ( 40 , 41 ). The phylogeny of all Cyanobacteria -classified OTUs and their two nearest neighbors in SILVA ( 42 ) indicated that the chloroplast and Oxyphotobacteria OTUs clustered in clades with chloroplast 16S rRNA genes of cultured eukaryotic algae ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A and B ). To better understand the relationship between the microbial guilds of Lake Cadagno, we sought phylogenetic evidence to support the origin of these putative chloroplast OTUs, as described in previous literature ( 40 , 41 ). The phylogeny of all Cyanobacteria -classified OTUs and their two nearest neighbors in SILVA ( 42 ) indicated that the chloroplast and Oxyphotobacteria OTUs clustered in clades with chloroplast 16S rRNA genes of cultured eukaryotic algae ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…M. polaris was discovered in the Canadian Arctic [ 3 , 61 ] and, as mentioned above, was shown to increase in abundance in association with climate-induced changes to the ecosystem [ 10 ]. M. polaris is also present in the Antarctic Ocean, according to amplicon, metagenomic, and qPCR studies [ 6 , 26 ]. It has been hypothesized that the presence of M. polaris in both Arctic and Antarctic waters could be explained by a possible connection between poles via the thermohaline processes responsible for the global ocean conveyor belt, specifically North Atlantic Deep Water (NADW) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amplicons were generated using the 16S rRNA V1-V2 primers 27F_ill (5′-TCGTCGGCAGCGTCAGATGTGTATAAGAGACAGagrgttygatymtggctcag-3) and 338R_ill (5′-GTCTCGTGGGCTCGGAGATGTGTATAAGAGACAGgcwgccwcccgtaggwgt-3′; capital letters represent Illumina linker sequences on the 27F/338R primer pair) as in [ 26 ] and purification was performed using a MinElute kit (Qiagen, Hilden, Germany). Amplicon products were sequenced using the Illumina Miseq platform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although polar oceans belong to one of the most productive and rapidly changing ecosystems on Earth 13 , the Southern Ocean remains poorly represented in these large surveys of marine protists. With the exception of a single small-scale study that examined protists in several deep-ocean water masses 14 , most studies of protists in the Southern Ocean focused on the photic layer [15][16][17][18][19][20][21] . Given the unique conditions during the polar winter, it is reasonable to assume that the heterotrophic lifestyle is of particular importance in the polar environment.…”
mentioning
confidence: 99%